KEGIATAN EKONOMI DAN SOSIAL PADA USAHA ONLINE DI KALANGAN MAHASISWA UNIVERSITAS RIAU PEKANBARU - Fernandus, Vincentius Fernandus; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This thesis is submitted in order to qualify holds a Bachelor of Sociology. With the title economic activities and social online business among students . the issues discussed in the thesis this is how economic activities online business among students and social relations in the business of online among students and how the benefits of running a business online among students. The subject in this study is 7 people. The samples used in this study is the snowball, this technique is the first sample and the next is obtained from information first sample. The method used is the method of research a qualitative because this method to explain every problem about this title is a descriptive. Instruments screening data used is an observation, a list of questions and documents. The theory used theory is social capital where to there is confidence, the network and norms. The results in general, the writer can say that students who conduct business online are basically to add to the needs of as a student, the subject in this study and of other people like a friend that come in online business is on the previous one never follow any business. Relations between resellers and customers not only through social media but offline. Sellers receive if a buyer who wants to meet to do the sale and purchase transactions. The importance of a social capital that must be held a reseller can help online business is in the technician can run smoothly. Capital, there are like trust, norms, and the network.Keyword : economic’s activities, benefits, online shop